RETRACTED: Investing in well-being: experiences of implementing the ESG agenda by Russian oil and gas companies - Daroshka Vitali; Aleksandrov Igor; Fedorova Marina; Petrov Maxim; Popazova Olga; Molodkova Eleonora (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001